H.A.S.I.S Printing Shoppe / Shamsudin Abas ... [et al.] - Abas, Shamsudin; Mazli, Mohd Hazly; Abdul Hamid, Mohamad Asrie; Mohd Ahkuan, Siti Nuratikah; Mohamad Amin, Sri Dayanie (Faculty of Information Management, 2003)
This paper work is about a business plan that we made based on the RETECH PRINTING COMPANY. With the information we have we create our company HASIS PRINTING SHOP. It is important to have a business plan before opening a business. HASIS PRINTING SHOP is located in Mid Valley, Petaling Jaya.